ETHNOBOTANICAL SURVEY OF HERBAL STEAM INHALATION (NYUNGU) IN ZANZIBAR: MEDICINAL PLANT USE, CULTURAL VALUE, AND TOURISM POTENTIAL - Juma, Bariki Salum; KHEIR , Khamis Rashid; RASHID , Rashid George; KHAMIS , Bilal Badrudin; ALI , Thani Ame; JUMA , Hassan Buda; KOMBO , Ussi Makame; MPATANI , Farid Mzee; MALEBO , Hamisi Masanja; SIMAI , Burhani Othman; JUMA , Amuor Khamis; JUMA , Bariki Salum (African Journal of Traditional, Complementary and Alternative Medicines, 2025)
Background: Traditional herbal steam inhalation (Nyungu) is a key healthcare practice in Zanzibar for treating respiratory, febrile, and spiritual ailments. Despite its importance, it remains under documented and underutilized in wellness tourism. This study aimed to document the medicinal plants used in Nyungu and explore opportunities for integration into tourism. Materials and Methods: A cross-sectional ethnobotanical survey was conducted in 26 shehias (14 in Unguja and 12 in Pemba). Sixty-eight traditional healers were purposively selected and interviewed using structured questionnaires. Data on plant use, preparation, treated ailments, and commercialization were analyzed using SPSS and Origin software. Results: The study identified 73 and 75 plant species in Unguja and Pemba, respectively. Commonly cited species included Citrus aurantiacus, Azadirachta indica, and Ocimum americanum. The main ailments treated were runny nose (18%), fever (15%), common cold (13%), and spiritual disorders (12%). Treatment regimens varied: most healers in Unguja preferred one-day sessions, while those in Pemba favored three- to seven-day duration. Polyherbal preparations were widely used. Commercialization was limited, with 60% of healers in Unguja and 84% in Pemba not offering services to tourists. Documentation was low, as only 8% (Unguja) and 17% (Pemba) recorded their practices. Conclusion: Nyungu remains a cornerstone of traditional healthcare in Zanzibar and holds promise for wellness tourism. However, poor documentation, limited commercialization, and lack of standardization hinder its development. Phytochemical validation, cultivation of key species, tourism integration, and supportive policies are recommended for sustainable use and cultural preservation.